2012
DOI: 10.5115/acb.2012.45.4.282
|View full text |Cite
|
Sign up to set email alerts
|

The double retro-aortic left renal vein

Abstract: The renal veins drain the kidney into the inferior vena cava and unite in a variable fashion to form the renal vein. The left renal vein is normally located in front of the aorta. However, the retro-aortic renal vein may course posterior to the aorta due to embryological developmental anomalies. During educational dissection, a rare variation of the left renal vein was found in a 66-year old male cadaver. The double retro-aortic renal veins coursed behind the aorta to drain into the inferior vena cava. The sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…However, the partial duplication type in this study differs from that of the previous study in its traversing dorsal to the aorta. The partial duplication type could relate to the origin of the supracardinal veins in the dorsolateral aspect of the aorta; this is feasible considering the possible persistence of the supracardinal veins at the caudal portion of the prerenal segment, as in the developments of different anomalies reported in humans . In addition, the previous study reported that in 50% of the partial duplication types, the left gonadal vein directly joins the left CVC .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the partial duplication type in this study differs from that of the previous study in its traversing dorsal to the aorta. The partial duplication type could relate to the origin of the supracardinal veins in the dorsolateral aspect of the aorta; this is feasible considering the possible persistence of the supracardinal veins at the caudal portion of the prerenal segment, as in the developments of different anomalies reported in humans . In addition, the previous study reported that in 50% of the partial duplication types, the left gonadal vein directly joins the left CVC .…”
Section: Discussionmentioning
confidence: 94%
“…The partial duplication type could relate to the origin of the supracardinal veins in the dorsolateral aspect of the aorta 33 ; this is feasible considering the possible persistence of the supracardinal veins at the caudal portion of the prerenal segment, as in the developments of different anomalies reported in humans. 34 In addition, the previous study reported that in 50% of the partial duplication types, the left gonadal vein directly joins the left CVC. 14 However, in our study, all of the partial duplication types showed the left gonadal vein joining the left renal vein.…”
Section: Single Left-sided Caudal Vena Cava Type: Left-sidednessmentioning
confidence: 98%
“…The mechanisms underlying left renal vein variations seem to be closely associated with the embryologic development of the abdominal renal vein. During the embryological period, two cardinal veins develop, forming an anastomosis ventral and dorsal to the aorta [10] , [11] . Usually, during the embryologic development and regression, the distal part of the IVC develops from the right subcardinal vein, and the left renal vein from the transverse ventral anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Renal vessels demonstrate huge anatomical variability as regards to their number, level of origin, diameter and topographical relationships [2, 8-10, 17, 19, 25, 26, 30-36]. In particular, it applies to the left renal vein which can present retroaortic [1,10,12,15] or even circumaortic placement [7,11,13,20,27]. Thus, the left renal vein may be a single vessel or double -with two limbs: one located anterior and the second posterior to the abdominal aorta [5,19,33].…”
Section: Introductionmentioning
confidence: 99%